Golgin Subfamily A Member 5 Is Essential for Production of Extracellular Matrix Proteins during TGF-β1-Induced Periodontal Ligament-Fibroblastic Differentiation - Hyun-Jin Kim; Seong-Min Kim; Min-Jeong Choi; Young-Joo Jang (Stem Cells International)
Human periodontal ligament stem cells (hPDLSCs) can be differentiated into periodontal ligament- (PDL-) fibroblastic progenitors by treatment with low concentrations of transforming growth factor beta 1 (TGF-β1). Although much is known about the profibrotic effects of TGF-β1, the molecular mechanisms mediating the activation of fibroblasts in periodontal ligament-fibroblastic differentiation are not well known. Our study was to investigate the mechanism of the fibroblastic process in the periodontal ligament differentiation of hPDLSCs through the discovery of novel markers. One of the monoclonal antibodies previously established through decoy immunization was the anti-LG11 antibody, which recognized Golgi subfamily A member 5 (GOLGA5) as a PDL-fibroblastic progenitor-specific antigen. GOLGA5/LG11 was significantly upregulated in TGF-β1-induced PDL-fibroblastic progenitors and accumulated in the PDL region of the tooth root. GOLGA5 plays a role in vesicle tethering and docking between the endoplasmic reticulum and the Golgi apparatus. siRNA-mediated depletion of endogenous GOLGA5 upregulated in TGF-β1-induced PDL-fibroblastic progenitors resulted in downregulation of representative PDL-fibroblastic markers and upregulation of osteoblast markers. When the TGF-β1 signaling pathway was blocked or GOLGA5 was depleted by siRNA, the levels of extracellular matrix (ECM) proteins, such as type I collagen and fibronectin, decreased in PDL-fibroblastic progenitors. In addition, Golgi structures in the perinuclear region underwent fragmentation under these conditions. These results suggest that GOLGA5/LG11 is a PDL-fibroblastic marker with functional importance in ECM protein production and secretion, which are important processes in PDL-fibroblastic differentiation.